Diabetic striatopathy - Silva Paredes, Elder (2024)
A 71-year-old male with a diagnosis of decompensated diabetes mellitus, who presents with involuntary movements in the right upper and lower limbs for the past two months. A non-contrast brain tomography was performed (A), which identified a faint hyperdensity in the left lentiform nucleus (arrow). This was complemented with a magnetic resonance imaging, and on the axial T1-weighted image (B), hyperintensity was observed in the left lentiform nucleus (arrow). Diabetic striatopathy, also known as non-ketotic hyperglycemia hemichorea, is a rare complication of diabetes mellitus, with the average age of onset being 71 years. Imaging findings are almost pathognomonic and show unilateral involvement of the striatum nucleus, contralateral to the affected side. Timely diagnosis and management are crucial as it may be completely reversible in a high percentage of patients.